RANCANG BANGUN SISTEM MONITORING KELEMBAPAN DAN PH TANAH YANG IDEAL UNTUK TANAMAN MENGGUNAKAN SMART DETECTOR - Al Qadri Kannang ,Abd Muin, Rossy Timur Wahyuningsih, Umar Katu, Nur Afif.. (Fakultas Teknik Universitas Muhammadiyah Makassar, 2025)
Abstrack- Modern agriculture increasingly adopts technology to enhance production efficiency and product quality. One crucial aspect of agriculture is monitoring soil conditions, especially moisture and pH, which significantly influence plant growth and health.Kata kunci : Monitoring Tanah, Kelembapan Tanah, pH Tanah, Smart Detector, Pertanian Berbasis Teknologi.